A mathematical model to evaluate hemodynamic effects of the graft anastomosis in coronary surgery - Ruvolo, Giovanni; Pisano, Calogera; Bertoldo, Fabio; Russo, Marco; Verzicco, Roberto; Nardi, Paolo (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2019)
The durability and patency of a coronary graft can be negatively affected by technical factors that induce thrombosis of the graft and poor prognosis of patients undergoing coronary artery bypass grafting. Technical factors include the inclination angle of the coronary anastomosis and the alignment between the main vessel and the inserted vessel as graft. We have studied a mathematical model aimed to assess the best angulation of the anastomosis and the influence of a correct alignment in order to prevent the risk of early graft occlusion. From data obtained from the mathematical model, in our opinion an inclination of the anastomotic angle of at least 30° seems to be a right choice when performing a coronary artery bypass graft. In addition, the incision of the coronary vessel should be done perfectly on the same axis as that performed on the graft, since even a deviation of the axis of the anastomosis of only 10° can create turbulence of the flow in the anastomosis site, which is accentuated when the deviation reaches 20°.